2006
DOI: 10.1038/nature04839
|View full text |Cite
|
Sign up to set email alerts
|

CRD-BP mediates stabilization of βTrCP1 and c-myc mRNA in response to β-catenin signalling

Abstract: Although constitutive activation of beta-catenin/Tcf signalling is implicated in the development of human cancers, the mechanisms by which the beta-catenin/Tcf pathway promotes tumorigenesis are incompletely understood. Messenger RNA turnover has a major function in regulating gene expression and is responsive to developmental and environmental signals. mRNA decay rates are dictated by cis-acting elements within the mRNA and by trans-acting factors, such as RNA-binding proteins (reviewed in refs 2, 3). Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
289
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(302 citation statements)
references
References 26 publications
6
289
4
3
Order By: Relevance
“…Although additional target mRNAs of IMP1 are expected, solid evidence indicates that IMP1 is essential for the regulation of c-myc, bTrCP1 and CD44 mRNA turnover, but also facilitates translational control of the IGF-II and b-actin mRNAs (Nielsen et al, 1999;Lemm and Ross, 2002;Huttelmaier et al, 2005;Noubissi et al, 2006;Vikesaa et al, 2006). While by the regulation of IGF-II and c-myc expression IMP1 is expected to affect cell proliferation, growth and survival, the regulation of CD44 or b-actin expression via IMP1 is suggested to modulate cell adhesion, invadopodia formation and actin dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although additional target mRNAs of IMP1 are expected, solid evidence indicates that IMP1 is essential for the regulation of c-myc, bTrCP1 and CD44 mRNA turnover, but also facilitates translational control of the IGF-II and b-actin mRNAs (Nielsen et al, 1999;Lemm and Ross, 2002;Huttelmaier et al, 2005;Noubissi et al, 2006;Vikesaa et al, 2006). While by the regulation of IGF-II and c-myc expression IMP1 is expected to affect cell proliferation, growth and survival, the regulation of CD44 or b-actin expression via IMP1 is suggested to modulate cell adhesion, invadopodia formation and actin dynamics.…”
mentioning
confidence: 99%
“…In human cancers, de novo synthesis of IMPs was identified in approximately 80% of colorectal carcinomas, 70% of bone and soft tissue sarcomas, 60% of breast carcinomas and 50% of non-small cell lung carcinomas (Ioannidis et al, 2001(Ioannidis et al, , 2003(Ioannidis et al, , 2004Ross et al, 2001). A pivotal role of IMP1 in colorectal cancer progression was emphasized by recent studies demonstrating that IMP1 mediates stabilization of the bTrCP1 mRNA in response to b-catenin signaling (Noubissi et al, 2006). In primary ovarian carcinoma, only one study reported an overexpression of IMPs based on semiquantitative reverse transcription-PCR (RT-PCR) analyses in carcinoma vs adenoma, but the functional role of IMP1 in ovarian carcinoma-derived cells was not evaluated (Gu et al, 2004).…”
mentioning
confidence: 99%
“…We identified the coding region determinantbinding protein (CRD-BP) as a novel transcriptional target of b-catenin, which binds and stabilizes b-TrCP1 mRNA in response to Wnt signaling (Noubissi et al, 2006). Elevated levels of b-TrCP1 result in increased activity of SCF bÀTrCP1 E3 ubiquitin ligase and accelerated degradation of its substrates, including IkBs.…”
mentioning
confidence: 99%
“…It protects MDR-1 mRNAs from endonucleolytic cleavage by binding to a coding region element (Sparanese and Lee, 2007). Also binds to the coding region of betaTrCP1 mRNA and stabilizes it by disrupting miRNAdependent interaction with AGO2 (Noubissi et al, 2006;Elcheva et al, 2009). Binds and stabilizes GLI1 mRNA causing an elevation of GLI1 expression and transcriptional activity ).…”
Section: Igf2bp1 (Insulin-like Growth Factor 2 Mrna Binding Protein 1)mentioning
confidence: 99%